The Influence of Green Transformational Leadership, Green Training, and Competency for Employee Performance - Anah, Sri; Robbi, Robbi (Universitas Mercu Buana, 2025)
Abstract. This study aims to analyze the effect of Green Transformational Leadership, Green Training and Competence on Employee Performance on employees of PT Bumi Berkah Boga. The objects in this study are employees of PT Bumi Berkah Boga with various ages who have worked in the company for a span of one to three years of work, domiciled in Jabodetabek, Indonesia. The research method used is quantitative research. The sample used in this study was 65 respondents. The sampling technique used purposive sampling and the approach used was the Structural Equation Model (SEM) with the Smart PLS analysis tool. The results showed that Green transformational leadership has a positive and significant effect on employee performance. Green training has a positive and significant effect on employee performance. Competence has a positive and significant effect on employee performance.